Deep immune profiling of ovarian tumors identifies minimal MHC-I expression after neoadjuvant chemotherapy as negatively associated with T-cell-dependent outcome. (1st January 2020) - Brunekreeft, Kim L.; Paijens, Sterre T.; Wouters, Maartje C.A.; Komdeur, Fenne L.; Eggink, Florine A.; Lubbers, Joyce M.; Workel, Hagma H.; Van Der Slikke, Elisabeth C.; Pröpper, Noor E.J.; Leffers, Ninke; Adam, Julien; Pijper, Harry; et al.
ABSTRACT: Epithelial Ovarian cancer (EOC) is the most lethal gynecological malignancy and has limited curative therapeutic options. Immunotherapy for EOC is promising, but clinical efficacy remains restricted to a small percentage of patients. Several lines of evidence suggest that the low response rate might be improved by combining immunotherapy with carboplatin and paclitaxel, the standard-of-care chemotherapy for EOC. Here, we assessed the immune contexture of EOC tumors, draining lymph nodes, and peripheral blood mononuclear cells during carboplatin/paclitaxel chemotherapy. We observed that the immune contexture of EOC patients is defined by the tissue of origin, independent of exposure to chemotherapy. Summarized, draining lymph nodes were characterized by a quiescent microenvironment composed of mostly non-proliferating naïve CD4 + T cells. Circulating T cells shared phenotypic features of both lymph nodes and tumor-infiltrating immune cells. Immunologically 'hot' ovarian tumors were characterized by ICOS, GITR, and PD-1 expression on CD4 + and CD8 + cells, independent of chemotherapy. The presence of PD-1 + cells in tumors prior to, but not after, chemotherapy was associated with disease-specific survival (DSS). Accordingly, we observed high MHC-I expression in tumors prior to chemotherapy, but minimal MHC-I expression in tumors after neoadjuvant chemotherapy, even though there were no differences in the number of tumor-infiltrating lymphocytes (TIL) in both groups. We therefore speculate that the TIL influx into the chemotherapy tumor microenvironment may be a consequence of the general inflammatory nature of chemotherapy-experienced tumors. Strategies to upregulate MHC-I during or after neoadjuvant chemotherapy may thus improve treatment outcome in these patients.